(untitled) (The Pakistan Development Review, 2020)
Notwithstanding the level of improvement in understanding the complexities of an economy, it is now well accepted that the ultimate incidence of various policy interventions leads to varied outcomes in terms of magnitude and persistence depending upon the structure of the economy. The objective of the present study is to disentangle the relative contributions of various exogenous and domestic shocks that contribute to business cycle fluctuations in Pakistan. The study is based on the New-Keynesian Open economy model, which is an extended version of (Gali & Monacili 2005). Keating’s two-step approach (1990, 2000) is employed to capture the dynamic behaviour of the variables of interest. Impulse response functions, along with forecast error variance decomposition analyses, are used to gain useful insights into the understanding of the transmission mechanism of policy and non-policy shocks. It is observed that fiscal policy does matter, at least in the short-run. The interest rate shock leads to the exchange rate appreciation thereby confirming the exchange rate puzzle. In response to adverse supply shocks, the Monetary Authority responds with a monetary contraction that prolongs the recessionary periods. Furthermore, it has a limited power to control inflation as inflation in Pakistan stems from supply-side factors as well as fiscal dominance. JEL Classification: C32, E52, E62, F41 Keywords: Open Economy, New Keynesian Model, Rational Expectations, Exchange Rate Puzzle